A Brief History of the Speed of Light before Einstein - Lazaroff-Puck, Cameron H. (Tufts Archival Research Center, 2005)
History of speed of light determinations from Ole Romer to Simon Newcomb as well as the evolving significance of this constant. The paper focuses on the contributions and effects on physics of six major figures in the scientific community beginning in the late 17th century and ending at the close of the 19th century, namely, Romer, Bradley, Fizeau, Foucault, Michelson and Newcomb.